KONSTRUKSI SKALA SOSIAL-EMOSIONAL UNTUK SISWA SMP - Ferisa Prasetyaning Utami; Ipung Hananto; Ni'matu Sholikhah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
his study aims to develop an instrument for adolescent social emotional skills in junior high schools. The urgency of this research is the need for a non-cognitive diagnostic assessment required by teachers to map the social emotional ability profile of junior high school students. The existence of appropriate assessment results will be the basis for providing learning strategies and school programs that are appropriate to the conditions of students. This research method uses a development method with a 3D model, namely define, design and develop. The validity of the instrument content is carried out by testing the instrument to experts / expert judgment and limited field testing to students in junior high schools in Magelang City. The population of this study is junior high schools in Magelang City with a sample of this study being 3 junior high schools in Magelang City with 2 classes each randomly determined by the Multistage Cluster Sampling sampling technique. The data analysis technique uses Aiken expert validity and uses Pearson Correlation for construct validity testing and Cronbach Alpha for instrument reliability. The results of the study showed that the Social Emotional scale for junior high school students had adequate validity and reliability, namely 28 items were declared valid and reliable with a Cronbach's Alpha coefficient of 0.796 > 0.6. ABSTRAK Penelitian ini bertujuan untuk mengembangkan instrumen keterampilan sosial emosional remaja di sekolah menengah pertama. Urgensi penelitian ini adalah kebutuhan akan asesmen diagnostik non cognitif yang diperlukan oleh guru untuk memetakan profil kemampuan sosial emosional siswa SMP. Adanya hasil asesmen yang tepat akan menjadi dasar dalam memberikan strategi pembelajaran maupun program sekolah yang sesuai dengan kondisi siswa. Metode penelitian ini menggunakan metode pengembangan dengan model 3 D yaitu define, desain dan develop. Validitas isi instrumen dilakukan dengan mengujikan instrumen kepada ahli / expert judgement dan uji lapangan terbatas kepada siswa-siswa di SMP Kota Magelang. Populasi Penelitian ini adalah SMP Se Kota Magelang dengan sampel penelitian ini adalah 3 sekolah SMP di Kota Magelang dengan masing-masing 2 kelas secara acak yang ditentukan dengan teknik sampling Multistage Cluster Sampling. Teknik analisis data menggunakan Aiken validitas ahli dan menggunakan Pearson Correlation untuk uji validitas konstruk dan Alpha Cronbach untuk reliabilitas instrumen. Hasil penelitian menunjukkan bahwa skala Sosial Emosional bagi siswa SMP memiliki validitas dan reliabilitas yang memadai yaitu sebanyak 28 item dinyatakan valid dan reliabel dengan koefisien Alpha Cronbach sebesar 0, 796 > 0,6.